Preservation of Anthocyanins in Postharvest Grapes Through Carboxymethyl Chitosan Films Containing Citrus Essential Oil Emulsion via Enzymatic Regulation - Xinye Wu; Haiying Wang; Yuan Zhou; Wei Xi; Yiqin Zhang; Shanshan Li; Jiaying Tang; Suqing Li; Qing Zhang; Yaowen Liu; Jingming Li; Mingrui Chen; et al. (Foods, 2025)
Carboxymethyl chitosan (CMCS) exhibits excellent film-forming capability but suffers from limited water resistance. To enhance hydrophobicity and antimicrobial properties, citrus essential oil was emulsified directly with citrus pectin and dispersed into the CMCS matrix. This study investigated the effects of varying emulsion concentrations (0, 1, 3, 5, and 7 wt%) on film performance. FT-IR, XRD, and SEM analyses confirmed uniform emulsion distribution within the CMCS matrix with favorable compatibility. Increased emulsion loading improved water resistance, antioxidant activity, and antimicrobial efficacy of the CMCS-based films, with the 3% emulsion concentration achieving optimal mechanical strength (TS: 4.09 MPa, EAB: 144.47%) and water vapor permeability (1.30 × 10−10 g·m·(Pa·s·m2)−1). Applied to grape preservation, the films significantly delayed quality deterioration of grapes. Furthermore, by modulating the activity of enzymes involved in anthocyanin metabolism, the films could effectively extend the shelf life of grapes by suppressing the oxidative degradation of anthocyanins.